2011
DOI: 10.1111/j.1365-4632.2011.04947.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for basal cell carcinoma in a southern Brazilian population: a case–control study

Abstract: The results of this study suggest that skin type and family history of skin cancer may be important in establishing risk for developing BCC. Additionally, the detection by clinical examination of skin markers related to UVR action is important in establishing which patients are more likely to develop BCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 8 publications
0
12
1
8
Order By: Relevance
“…Although the markers of interest used in this study were not prone to recall bias, in most studies it was unclear if observers were blinded to skin cancer status before examination, potentially resulting in biased assessments (47)(48)(49)(50)(51). The most likely result of this would have been to overestimate the association between chronic skin damage and BCC.…”
Section: Discussionmentioning
confidence: 75%
“…Although the markers of interest used in this study were not prone to recall bias, in most studies it was unclear if observers were blinded to skin cancer status before examination, potentially resulting in biased assessments (47)(48)(49)(50)(51). The most likely result of this would have been to overestimate the association between chronic skin damage and BCC.…”
Section: Discussionmentioning
confidence: 75%
“…Indeed, some studies showed no effect of sunscreen use on BCC prevention. In a case-control Italian study [178], the frequent use of sunscreens entailed a non-significant protective effect (OR 0.6, 95% CI 0.3-1.4) and a recent Brazilian case-control study carried out in subjects aged 18-80 years found no effect of sunscreen or protective clothing use on BCC risk [179]. Finally, two cohort studies did not show a decrease in SCC or BCC risk with sunscreen use after adjusting for skin phenotype and sun-exposure [180,181].…”
Section: Preventionmentioning
confidence: 94%
“… 3 , 20 Other environmental factors which related to increased incidence of skin cancers were the ozone layer depletion and living in high altitude, low latitude areas. 22 Among individual risk factors, 9 , 12 , 20 , 21 fair skin, age above 40 years, genetic predisposition (albinism, xeroderma pigmentosum, epidermodysplasia verruciformis, and basal-cell nevus syndrome), and immunosuppression. Absent or improper skin protection during professional activities or leisure times allows for sunburns, mainly during childhood and adolescence, which leads to increased skin cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 20 Outros fatores ambientais relacionados à maior incidência de câncer de pele são a redução da camada de ozônio e viver em regiões de alta altitude e baixa latitude. 22 Entre os fatores de risco individuais, 9 , 12 , 20 , 21 encontram-se pele clara, idade acima de 40 anos, predisposição genética (albinismo, xeroderma pigmentoso, epidermodisplasia verruciforme e síndrome do nevo basocelular) e imunossupressão. A ausência ou a inadequada proteção da pele nas atividades laborais e nos momentos de lazer propiciam queimaduras solares, principalmente na infância e adolescência, o que leva ao aumento do risco de câncer de pele.…”
Section: Introductionunclassified